(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Facies and biostratigraphic analyses of the Contrada Diesi succession, cropping out along the northern slope of Mt. Magaggiaro (Sciacca, SW Sicily), provided new data on the Middle Jurassic-Early Cretaceous pelagic sedimentation in the Saccense domain. The richness in ammonites allowed the identification of Bathonian-Kimmeridgian Biozones and Subzones, while the Tithonian-Valanginian interval was defined mainly by calpionellids and calcareous nannofossils. Facies and microbiofacies analyses of the Jurassic-Cretaceous pelagic sediments of the area, together with ammonite, calpionellid and calcareous nannofossil integrated biostratigraphy, were very effective tools for comparison of biostratigraphic events. Many gaps in sedimentation were recognized, the most important spanning the middle and late Berriasian and part of the early Berriasian. The Contrada Diesi succession provides new litho-biostratigraphic data on the Saccense Domain. It suggests a high degree of internal variability tied to the irregular paleotopography of the carbonate platform substrate (Inici Fm.), derived from Early Jurassic tectonics. Gaps in sedimentation in the Contrada Diesi sections indicate that the environment of the Saccense Domain was characterized by a variable rate of sedimentation and energy changes.